COMPARISON OF ESTIMATION OF REINFORCED CONCRETE STRUCTURE WORKING COSTS BASED ON THE CONCEPT OF COMPUTER-AIDED DESIGN (CAD) AND BUILDING INFORMATION MODELING (BIM) - Intan Rahmani; Bambang Herumanta (International Journal Labs, 2022)
The cost estimation process is an important aspect of project management. In line with industry 4.0 development, a new concept called building information modeling (BIM) was introduced. However, in the Indonesia construction sector itself, the application of the BIM concept is still not optimal. Many construction actors still using conventional concept using computer aided design (CAD) drawing in estimating project cost. This case study aims to compare the project cost estimation between conventional calculation based on CAD drawing dan calculation with the BIM concept. This case study was designed with quantitative approach where the unit price analysis will refer to The PUPR regulation no 1 of 2022. From the result, it was found that the project cost estimation using conventional calculation based on CAD drawing was Rp.39.249.184.000 meanwhile the project cost estimation based on BIM concept was Rp.38.978.799.000 It can be concluded that the calculation using the BIM concept result a lower cost estimation of RP.270.385.000 or worth 0,69% compared to the cost estimation based on conventional calculation.